Pengaruh Model Pembelajaran Learning Cycle Terhadap Kemampuan Menulis Teks Persuasi Pada Siswa - Henny Dheana Putri; Azhar Umar (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
This study aims to determine the cooperative learning model of the Learning Cycle type on the ability to write persuasive texts in class VIII students of SMP Negeri 8 Medan in the 2022/2023 Academic Year. The population in this study were all Grade VIII students of SMP Negeri 8 Medan for the 2022/2023 academic year with a total of 304 students. Of the 304 students, the sample size was 30 students. The research method used in this research is the one-group pre-test post-test design experimental method. The instrument used in this study is a description test. Hypothesis testing was carried out using the data "t" test and it was found that the ability to write persuasive texts of students before using the Learning Cycle learning model was included in the sufficient category with an average value (mean) of 53.83, while the ability to write persuasive texts of students after using the model Learning Cycle learning increased with an average value (mean) of 81.16. Furthermore, the hypothesis test shows that tcount > ttable, which is equal to 13.14 > 2.045, it is concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is an effect of the Learning Cycle learning model on the ability to write persuasive texts in class VIII students of SMP Negeri 8 Medan in the 2022/2023 academic year.